Cost analysis of substitutive renal therapies in children - Maria Fernanda Carvalho de Camargo; Klenio de Souza Barbosa; Seiji Kumon Fetter; Ana Bastos; Luciana de Santis Feltran; Paulo Cesar Koch-Nogueira (Jornal de Pediatria, 2018)
Objective: End-stage renal disease is a health problem that consumes public and private resources. This study aimed to identify the cost of hemodialysis (either daily or conventional hemodialysis) and transplantation in children and adolescents. Methods: This was a retrospective cohort of pediatric patients with End-stage renal disease who underwent hemodialysis followed by kidney transplant. All costs incurred in the treatment were collected and the monthly total cost was calculated per patient and for each renal therapy. Subsequently, a dynamic panel data model was estimated. Results: The study included 30 children who underwent hemodialysis (16 conventional/14 daily hemodialysis) followed by renal transplantation. The mean monthly outlay for hemodialysis was USD 3500 and USD 1900 for transplant. Hemodialysis costs added up to over USD 87,000 in 40 months for conventional dialysis patients and USD 131,000 in 50 months for daily dialysis patients. In turn, transplant costs in 50 months reached USD 48,000 and USD 70,000, for conventional and daily dialysis patients, respectively. For conventional dialysis patients, transplant is less costly when therapy exceeds 16 months, whereas for daily dialysis patients, the threshold is around 13 months. Conclusion: Transplantation is less expensive than dialysis in children, and the estimated thresholds indicate that renal transplant should be the preferred treatment for pediatric patients. Resumo: Objetivo: A Doença Renal em Estágio Final é um problema de saúde que consome recursos públicos e privados. Nosso objetivo é identificar o custo da hemodiálise (hemodiálise diarias ou convencional) e transplante em crianças e adolescentes. Métodos: Uma coorte retrospectiva de pacientes pediátricos com Doença Renal em Estágio Final (DREF) submetidos à hemodiálise após transplante de rim. Todos os custos incorridos no tratamento foram cobrados e o custo total mensal foi calculado por paciente e por cada terapia renal. Então, foi estimado um modelo dinâmico com dados em painel. Resultados: Estudamos 30 crianças submetidas à hemodiálise (16 hemodiálises convencionais/14 hemodiálises diárias) após transplante renal. O gasto médio mensal para hemodiálise foi US$3,5 mil e US$1,9 mil para transplante. Os custos de hemodiálise somam mais de US$87 mil em 40 meses para pacientes submetidos a hemodiálise convencional (HC) e US$131 mil em 50 meses para pacientes submetidos a hemodiálise diária (HD). Por outro lado, os custos de transplante em 50 meses atingem US$48 e US$70 mil, para pacientes submetidos a HC e HD, respectivamente. Para pacientes submetidos à hemodiálise convencional, o transplante é menos oneroso quando a terapia ultrapassa 16 meses, ao passo que para pacientes submetidos a hemodiálise diária o limiar é cerca de 13 meses. Conclusão: O transplante é menos caro que a diálise em crianças e os limiares estimados indicam que o transplante renal deve ser o tratamento preferencial para pacientes pediátricos. Keywords: Economics, Kidney transplantation, Renal dialysis, Pediatrics, Palavras-chave: Economia, Transplante renal, Diálise renal, Pediatria